Patriarchal Resistance of Female Characters in There’s Still Tomorrow (2023) - Angelica Sanjaya; Ephrilia Noor Fitriana (Journal of English Language and Education, 2026)
Patriarchy continues to shape women’s roles and limit their opportunities across social and economic structures. However, existing studies often focus on symbolic and institutional forms of resistance, overlooking the material conditions that sustain women’s oppression. This study aims to analyze the representation of patriarchal power and women’s resistance in There’s Still Tomorrow (2023) using Silvia Federici’s Marxist feminist framework. This research employs a qualitative descriptive method by examining selected scenes and dialogues related to domestic labor, economic control, bodily regulation, and resistance. The findings reveal that patriarchal power operates through economic dependency, control over women’s bodies, and unequal access to resources. At the same time, women’s resistance emerges as the dominant pattern through everyday survival strategies, such as emotional endurance, small acts of defiance, and attempts to gain autonomy within domestic life. However, such resistance remains constrained within the patriarchal-capitalist system. Therefore, the study concludes that resistance exists but functions primarily as a survival strategy rather than a structural transformation.